2006
DOI: 10.3354/dao072077
|View full text |Cite
|
Sign up to set email alerts
|

A non-lethal technique for detecting the chytrid fungus Batrachochytrium dendrobatidis on tadpoles

Abstract: Batrachochytrium dendrobatidis (Bd) infection on post-metamorphic frogs and salamanders is commonly diagnosed using polymerase chain reaction (PCR) of skin scrapings taken with mildly abrasive swabs. The technique is sensitive, non-lethal, and repeatable for live animals. Tadpoles are generally not sampled by swabbing but are usually killed and their mouthparts excised to test for the pathogen. We evaluated a technique for non-lethal Bd diagnosis using quantitative PCR (qPCR) on swabs scraped over the mouthpar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“…While cotton-tipped, wire swabs (e.g. Medical Wire & Equipment MW 100−100) are a common collection tool, toothpicks have been used successfully in previous studies to collect Bd from amphibians (Retallick et al 2006, Woodhams et al 2006, Retallick & Miera 2007, Hyman & Collins 2012. Despite the popularity of wire swabs, there is no evidence demonstrating that wooden toothpicks are any better or worse at collecting Bd.…”
Section: Contemporary Surveymentioning
confidence: 95%
See 2 more Smart Citations
“…While cotton-tipped, wire swabs (e.g. Medical Wire & Equipment MW 100−100) are a common collection tool, toothpicks have been used successfully in previous studies to collect Bd from amphibians (Retallick et al 2006, Woodhams et al 2006, Retallick & Miera 2007, Hyman & Collins 2012. Despite the popularity of wire swabs, there is no evidence demonstrating that wooden toothpicks are any better or worse at collecting Bd.…”
Section: Contemporary Surveymentioning
confidence: 95%
“…It is important to note, however, that metrics of zoospore load are associated with substantial variation related to sampling protocol. Different researchers swab differently -some swab more thoroughly or with greater pressure than those with a lighter hand or less skill (Retallick et al 2006) -but there is probably a species, life stage, or even an individual host effect. Recent research found that zoospore load variation could not be explained solely by species, nor habitat, climate, or elevation; zoospore load may be entirely an individual host characteristic (Gründler et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tadpoles from 4 of the 13 species encountered (Table 1), namely Microhyla achatina, M. palmipes, Megophrys montana and Philautus aurifasciatus, were not examined because of the natural absence of an oral disk in the first 3 species and the absence of a tadpole stage in the last species. Examination of tadpole mouthparts has been used to indicate the likelihood of chytridiomycosis in several species (Knapp & Morgan 2006, Retallick et al 2006. Only one tadpole that showed abnormalities in its mouthparts was swabbed for PCR testing.…”
Section: Methodsmentioning
confidence: 99%
“…Sampling was performed by gently stroking flat wooden toothpicks (see Retallick et al 2006) across the toes, webbing, feet, thighs, sides and abdomen of the frogs (Briggs & Vredenberg available at http://amphibiaweb.org/ chytrid/swab_instruction.pdf, Livo 2004 at http:// wildlife.state.co.us/NR/rdonlyres/710BBC95-2DCF-4CF9-8443-D4561 DBC3B 69/0/PCRsampling2004.pdf), with a minimum of 20 strokes per individual. Toothpicks were then stored in 2 ml Axygen screw-cap tubes (with rubber o-rings) filled with 1 ml 70% ethanol.…”
Section: Methodsmentioning
confidence: 99%